Cutaneous blastic plasmacytoid dendritic cell neoplasm: Report of a case and review of the literature - Lin, Chien-yio; Wu, Ming-Ying; Kuo, Tseng-tong; Lu, Pei-Hsuan (Zhonghua pi fu ke yi xue za zhi, 2017)
Abstract Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematologic malignancy that usually occurs in elderly individuals and manifests with skin lesions followed by involvement of the lymph nodes, bone marrow, and peripheral blood. We report our experience of establishing the diagnosis of a case of BPDCN in an 86-year-old man. The related literature is reviewed, and the differential diagnosis and treatment modality of this rare entity are discussed.